From Sacred to Shared: A Quantitative Study of Wedding Hashtag Use and the Transformation of Marriage Meaning - Syahrul Hidayanto; Wa Ode Sitti Nurhaliza; Wichitra Yasya; Dinah Hernandez (Palakka : Media and Islamic Communication, 2026)
The rise of social media has transformed how individuals represent significant life moments, including marriage. One emerging practice in the digital era is the use of personalized wedding hashtags, which serve not only as tools for digital archiving but also as symbols of identity, image, and social engagement. This transformation reflects a cultural shift in which marriage has evolved from a sacred and private ritual into a public and performative event shared in digital spaces. This study examines the relationship between the intensity of wedding hashtag usage and the shifting meaning of marriage in the social media era among married social media users in Indonesia. Using a quantitative approach, data were collected through an online survey involving 422 respondents who had experience using personalized wedding hashtags. The Pearson correlation test revealed a strong and significant relationship between the two variables (r = 0.656, p < 0.001), with a determination coefficient of 43.1%. These findings indicate that nearly half of the variance in the shifting meaning of marriage can be explained by hashtag usage intensity. Within the framework of Media System Dependency Theory (MSDT), the study concludes that individuals who depend on social media for orientation and social validation are more likely to reinterpret institutional values such as marriage.